Identifying birth places of high-velocity stars - Hambaryan, V.
We searched for the high-velocity and isolated neutron stars that encountered in the past with a stellar cluster/association closer than 20 pc. We took about 830000 stars with the high-quality astrometry and radial velocities from the Gaia DR2 catalogue and empirically selected about 560 high-velocity stars. We used a full gravitational potential of the Galaxy to calculate the motion of a stellar cluster/association and a candidate of high-velocity star from their current positions to the proximity epoch. For these calculations we used a numerical integration in rectangular, Galactocentric coordinates. We used a covariance matrices of the astrometric data for each star to estimate the accuracy of the obtained proximity distance and epoch. For this aim we used a Monte Carlo method, replaced each star with 10 000 of its simulations and studied the distribution of their individual close passages near a stellar cluster/association. In addition, we investigated a neutron star/runaway star pairs very likely both ejected from binary system during supernova event.
Keywords: Stellar Astrophysics